Tennis: a promising approach to family-centered physical activity and health promotion - Dombrowski, Nicholas; Hanson , Jennifer Ann (My University, 2021)
Despite global goals to reverse the prevalence of obesity and inactivity, little to no progress has been made. This article presents the details of a tennis-based, family-centered program that can serve as a model for future wellness interventions. The program succeeded in providing a source of physical activity for the children and adults involved. Participant feedback confirmed that the program was well received and that an expanded program would be feasible. Tennis appears to be a viable platform for health promotion, and tennis professionals looking to build partnerships for the purpose of growing the game should keep in mind potential public health stakeholders.
Keywords: Racket sports; Nutrition; Wellness; Family; Physical activity